Sappan (Caesalpinia Sappanl.) Extract-Based Label for Detection of Chicken Meat Spoilage - Muhammad Fakih Kurniawan; Tiana Fitrilia; Hikmah Nur Chosida; Nursyawal Nacing (Universitas Djuanda, 2021)
Brazilin in sappan is sensitive to pH, which make it possible as indicator of food quality. This research aimed to investigate performance of sappan extract as colorant for indicator label applied in chicken meat packaging. The samples were stored at room and refrigerator temperature. They were then tested for color change of label RGB (Red Green Blue), pH and TVB-N (Total Volatile Base-Nitrogen) of the meat. Data were analyzed using ANOVA at significant level of 5%. Indicator label showed the reduced RGB during storage, while pH and TVB-N increased. In case of room temperature, the color change into pink occurred in day 3 with pH 6.72 and TVB-N 1.84 mg N/100g. Meanwhile, for samples at refrigerator temperature, the label color turned into pink in day 6, with pH 6.56 and TVB-N 2.09 mg N/100g. In this regard, indicator label could detect the depletion of chicken meat quality as indicated by color shift from yellow to pink when pH and TVB-N were at critical value. This result provides significant output for development of sappan extract for indicator of meat spoilage.